KONSEP DASAR KEPEMIMPINAN DALAM PENDIDIKAN ISLAM - Labaso’, Syahrial (Al Ghazali, 2018)
Leadership is the most basic thing in organizational management, includingin the field of education. Through a good leadership process, the goals and idealsof the organization can be more easily achieved and realized. This articleexamines conceptually the process of implementing leadership in Islamiceducation. This is seen as important, because the progress and decline of thequality of education is very dependent on the extent to which a leader can carry out his duties and leadership role effectively and efficiently. In this paper, it is found that the fundamental difference between leadership in general, and leadership in Islamic education. That general leadership only focuses on the answer of a leader towards members of the organization. But it is different in Islamic education, which understands that leadership is the task of the Caliphate which emphasizes the importance of answers not only to the members they lead, but also to God Almighty as a source of authority.